2004
DOI: 10.1080/01650250344000370
|View full text |Cite
|
Sign up to set email alerts
|

Parenting behaviours during child problem solving: The roles of child temperament, mother education and personality, and the problem-solving context

Abstract: Child temperament, parent openness to experience, conscientiousness, and education, and parent a priori assessments of the task were examined in relation to parenting behaviours during child problem solving. Mothers and their children (73 dyads) were visited the summer before kindergarten. Mothers' cognitive, emotional, and autonomy support were coded as they provided assistance during four child problem-solving tasks. Mothers with more education provided more metacognitive information. Before education was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
73
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 58 publications
9
73
0
6
Order By: Relevance
“…Although a child's difficult temperament is likely to elicit irritable and punitive responses from parents, this does not always hold true (Lemery and Goldsmith 2002;Meyers 1999;Neitzel and Stright 2004). Rather, some parents still provide warm and appropriate parenting toward a child who is emotionally irritable and socially inhibited (Rubin et al 1998;Thomas and Chess, 1984).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Although a child's difficult temperament is likely to elicit irritable and punitive responses from parents, this does not always hold true (Lemery and Goldsmith 2002;Meyers 1999;Neitzel and Stright 2004). Rather, some parents still provide warm and appropriate parenting toward a child who is emotionally irritable and socially inhibited (Rubin et al 1998;Thomas and Chess, 1984).…”
Section: Discussionmentioning
confidence: 90%
“…Rather, some parents still provide warm and appropriate parenting toward a child who is emotionally irritable and socially inhibited (Rubin et al 1998;Thomas and Chess, 1984). Alternatively, a plausible explanation for the nonsignificant relation between child temperament and parenting styles centers around the potential moderating role of maternal education, as Neitzel and Stright (2004) suggested. Indeed, they showed that mothers with higher levels of education were more likely to be emotionally and cognitively supportive toward their young children if they perceived their children as difficult.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…More elaborate and facilitating strategies occurred in the activities that they perceived as learning opportunities for children and where adults' support was thought to be necessary (Gonzalez, 1996;Neitzel and Stright, 2004). Variations of adults' behaviors in different tasks may also be affected by their familiarity with the task (Goodsitt et al, 1988).…”
Section: The Nature Of Scaffoldingmentioning
confidence: 99%